Electricity across the border : the U.S.-Canadian experience - Perlgut, Mark. ([Montreal] : Canadian-American Committee, 1978)
This book explore the relationship between the Canadian - American electricity interconnections which was inaugurated during the first year of the century
"CAC 47."
"An executive summary" ([4] p.) laid in.
Includes bibliographical references.
ijb, 14/01/2019
Loans
Keywords: Electric utilities; Electric utilities; International interconnected electric utility systems; International interconnected electric utility systems